Carbon dioxide as a substrate in the Staudinger-aza-Wittig reaction leading to new sugar surfactants with potential use in cosmetics industry - Karolina Koselak; Marcin Kozanecki; Sławomir Kadłubowski; Stanisław Porwański (Journal of CO2 Utilization)
In this study we presented the preparation of eleven unknow in the literature surfactants based on mono- and disaccharides which contained urea bridge and 10, 12 or 14 carbon atoms in the hydrophobic chain in their structure. The surfactants were obtained in the SAW reaction in which CO2 is used as one of the substrates with yields ranging from 16 % to 99 %. Some of the physicochemical properties were also investigated. The sugar derivatives are not soluble in water but shortening the hydrophobic chain to 8 carbon atoms increased their solubility. The HBL parameter indicated that the obtained surfactants are, among others, detergents, emulsifiers and wetting agents, which is also confirmed by results of the contact angle study. Compounds 29 forms aggregates or maybe even micelles above concentration of 1 mmol/l. The compounds also exhibit physical gel forming properties.